Attitudes toward Suicide among Individuals involved in Suicide Care in Chiang Mai and Khon Kaen provinces, Thailand - Kriengtuntiwong, Thuvachit; Longchoopol, Chaowanee; Thapinta, Darawan; Butrin, Wanida; Poodankang , Sangob; Janthakun , Putthichada; Piyaphattarakul , Sirirat (Academic Psychiatry and Psychology Journal, 2025)
Objective: To study the attitudes toward suicide among individuals involved in the care of people with suicidal behavior in Chiang Mai and Khon Kaen Provinces, Thailand Methods: This qualitative study employed semi-structured in-depth interviews. Informants from each province included public health personnel, religious leaders, and caregivers of individuals who had attempted suicide. Data were collected in Chiang Mai at Sansai Hospital (13 participants) and in Khon Kaen at Khon Kaen Rajanagarindra Psychiatric Hospital (14 participants) between July and September 2023. The questionnaire was developed by the researchers based on a review of relevant literature and was validated by experts. Data were analyzed using content analysis. Results: The causes of suicide were perceived to stem either from impulsive emotions or from well-considered decisions. Some participants believed that suicide is a personal right, while others thought that no one has the right to take their own life. When a family member dies by suicide, it leaves emotional wounds and a sense of guilt among those left behind. The role of religion in preventing suicide was seen as dependent on individual perspectives. Family members can help prevent suicide by engaging in conversation and offering emotional support to the person at risk. Conclusion: Different attitudes and religious beliefs toward suicide can influence its prevention. Public health personnel should provide caregivers with accurate perspectives to enhance the effectiveness of suicide prevention efforts outside of hospital settings.